2008
DOI: 10.1259/bjr/96187638
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic phased-array MR imaging of anal carcinoma before and after chemoradiation

Abstract: The aim of this study was to evaluate the MR findings of anal carcinoma using an external pelvic phased-array coil before and after chemoradiation treatment. 15 patients with carcinoma of the anal canal underwent T(2) weighted and short-tau inversion recovery (STIR) imaging before and after chemoradiation. Images were reviewed in consensus by two radiologists. At pre-treatment imaging, the tumour size and stage, signal intensity and infiltration of adjacent structures were recorded. MR imaging was repeated imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 8 publications
1
48
1
4
Order By: Relevance
“…Studies have shown good agreement in local tumour staging by MRI versus clinical digital examination [15].…”
Section: Role Of Mrimentioning
confidence: 96%
See 3 more Smart Citations
“…Studies have shown good agreement in local tumour staging by MRI versus clinical digital examination [15].…”
Section: Role Of Mrimentioning
confidence: 96%
“…7). Extension laterally into the ischiorectal fat is less common, suggesting that the levators act as a barrier to lateral tumour growth [15].…”
Section: Role Of Mrimentioning
confidence: 99%
See 2 more Smart Citations
“…L'IRM pelvienne est systématique pour certaines équipes. Elle est surtout intéressante pour les tumeurs plus volumineuses car elle est sans doute plus précise que l'échoendoscopie pour préciser les rapports avec les organes et structures de voisinage et pour rechercher des adénopathies à distance [3].…”
Section: ❚ Introductionunclassified